IMAGERY AND FIGURATIVE LANGUAGE IN WILLIAM WORDSWORTH POEM ENTITLED “RESOLUTION AND INDEPENDENCE” - Tahani (MABASAN, 2023)
Poems are carefully crafted things in words, unlike everyday speech or writing. A poem's special component, imagery and figurative language are both present. The aim of this study is to reveal the imagery and the figurative language in the poem resolution and independence by William Wordsworth. The researcher uses qualitative method with content analysis technique because the data collected are in the form of words. After analysing the data, it is found that there are two common types of imagery which are visual and auditory imagery. The researcher also finds personification, simile, and symbolism, the common type of figurative languages, in the lyric of the poem. The unique natural items like sky, mist, clouds, stone, and rock; animals like hares and sea-beast; and natural events have evolved into the main subjects of these figurative languages. Wordsworth is imposing his own emotions and sentiments onto the object and the natural events in this poem.